Understanding young peoples' and family members' views of treatment for first episode psychosis in a randomised controlled trial (MAPS). (July 2020) - Byrne, R.E.; Bird, J.C.; Reeve, S.; Jones, W.; Shiers, D.; Morrison, A.P.; Pyle, M.; Peters, S.
Abstract: Background: There is limited evidence to inform treatment decision-making in adolescents experiencing first episode psychosis (FEP). In the MAPS trial (Managing Adolescent first Episode Psychosis: a feasibility Study), adolescents with FEP received either antipsychotic medication (AP), psychological intervention (PI), or both. We investigated treatment views of young people and family members across each treatment arm of MAPS. Methods: Thirteen adolescents participating in MAPS and eighteen family members attended in-depth audio-recorded interviews to discuss trial treatments. Interviews were analysed using inductive Thematic Analysis, identifying salient themes across these accounts. Findings: Family members in particular reported an urgent need for treatment regardless of type. Both AP and PI were broadly viewed as acceptable treatment approaches, but for differing reasons which participants weighed against a range of concerns. AP were often seen to reduce symptoms of psychosis, though participants expressed concerns about side effects. PI were viewed as interactive treatment approaches that helped improve understanding of psychosis and enhanced coping, although some found PI emotionally and cognitively challenging. Combining treatments was seen to maximise benefits, with a perceived interaction whereby AP facilitated engagement with PI. Interpretation: Acceptability of and engagement with treatments for FEP may differ between individual young people and their family/carers. In order to be able to offer fully informed choices, and determine an optimum treatment approach for young people with FEP, definitive trial evidence should be established to determine wanted and unwanted treatment impacts. Funding: NIHR HTA programme (project number 15/31/04).